2022
DOI: 10.1002/acn3.51517
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore 16S sequencing enhances the detection of bacterial meningitis after neurosurgery

Abstract: Objective: Nosocomial bacterial meningitis is one of the major complications after neurosurgery. We performed nanopore 16S amplicon sequencing from cerebrospinal fluid (CSF) to evaluate bacterial meningitis in patients who underwent neurosurgery. Methods: Among the patients who visited the neurosurgery department of Seoul National University Hospital between July 2017 and June 2020, those with clinically suspected bacterial meningitis were included. 16S rDNA PCR was performed from the CSF, and nanopore sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Our study demonstrated the potential of 16S rRNA gene PCR/sequencing (30% of tested, culture negative CSF samples were positive) that can identify the presence of bacteria even in patients who have already received antibiotics [ 14 , 15 , 16 ]. This method can also provide more rapid identification, especially of slow-growing and fastidious bacteria [ 17 , 18 ]. Multiple studies on broad range PCR methods in HCAMV report high specificity and often limited sensitivity [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated the potential of 16S rRNA gene PCR/sequencing (30% of tested, culture negative CSF samples were positive) that can identify the presence of bacteria even in patients who have already received antibiotics [ 14 , 15 , 16 ]. This method can also provide more rapid identification, especially of slow-growing and fastidious bacteria [ 17 , 18 ]. Multiple studies on broad range PCR methods in HCAMV report high specificity and often limited sensitivity [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the strong capacity of pathogen detection, NTS should be recommended to be used in CSF for diagnosing CNS infection. Supporting our view, a pilot study including six retrospective cases of confirmed bacterial meningitis and two prospective cases showed that the NTS was more sensitive than conventional culture and worked properly even in samples exposed to antibiotics ( 25 ). Another study showed that the diagnostic sensitivity of the NTS and culture was 100% and 44.9%, respectively, for the genuine CNS infection ( 26 ).…”
Section: Discussionmentioning
confidence: 72%
“…Cerebrospinal fluid (CSF) analysis is currently considered the gold standard for diagnosing intracranial infections, and biomarkers such as CSF lactate, heparin-binding protein, C-reactive protein, and procalcitonin play ancillary roles [ 46 49 ]. With the development of molecular biology, laboratory diagnostic tools have evolved from the cellular to the molecular DNA levels [ 50 , 51 ]. Pathogenic high-throughput genetic testing enables the rapid detection of disease-causing microorganisms.…”
Section: Literature Review and Discussionmentioning
confidence: 99%